2017
DOI: 10.1155/2017/7473437
|View full text |Cite
|
Sign up to set email alerts
|

Collagen External Scaffolds Mitigate Intimal Hyperplasia and Improve Remodeling of Vein Grafts in a Rabbit Arteriovenous Graft Model

Abstract: Objectives. The aim of this study was to test the effects of collagen external scaffold (CES) in intimal hyperplasia of vein grafts and explore its underlying mechanisms. Methods. Thirty-six New Zealand white rabbits were randomized into no-graft group, graft group, and CES group. The rabbit arteriovenous graft model was established. In CES group, the vein graft was wrapped around with CES. The hemodynamic parameters of vein grafts were measured intraoperatively and 4 weeks after operation by ultrasonic examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…25 In our previous studies, we found that higher blood flow could improve the hemodynamic stability of vein grafts, and the specific mechanism may be that it could mitigate intimal hyperplasia and improve remodeling of venous grafts, which may be associated with reducing the proliferation and apoptosis and preserving the phenotype of vascular smooth muscle cell. 26 In our study, we also found that the higher the blood flow, the higher the patency. The blood flow of LAD was the highest in the target vessels, and its patency was more than 90%, especially the patency of LIMA-LAD was as high as 96.11%.…”
Section: Discussionsupporting
confidence: 70%
“…25 In our previous studies, we found that higher blood flow could improve the hemodynamic stability of vein grafts, and the specific mechanism may be that it could mitigate intimal hyperplasia and improve remodeling of venous grafts, which may be associated with reducing the proliferation and apoptosis and preserving the phenotype of vascular smooth muscle cell. 26 In our study, we also found that the higher the blood flow, the higher the patency. The blood flow of LAD was the highest in the target vessels, and its patency was more than 90%, especially the patency of LIMA-LAD was as high as 96.11%.…”
Section: Discussionsupporting
confidence: 70%
“…[25][26][27][28][29][30][31] Only an autologous venous graft model in rabbits has been reported, in which an excised external jugular vein graft was anastomosed to replace a removed segment of the ipsilateral common carotid artery in an end-to-end manner. 32,33 Therefore, our 3D-printed AVG should be examined for a long-term patency rate using the large animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation within the vascular wall is a hurdle, and manipulating the inflammatory cytokines and chemokines is possibly the key piece in solving the puzzle. Other than that, research related to inhibition of intimal hyperplasia has also been extensively done using various approaches, which utilized gene therapy and vector-mediated gene delivery [ 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], anti-inflammatory and anti-proliferative drugs [ 57 ], compounds with anti-inflammatory actions such as plants [ 55 , 65 ], herbal medications [ 50 ], marine sources [ 52 ] and polyunsaturated fatty acids [ 56 ].…”
Section: Discussionmentioning
confidence: 99%